Instruments for assessing Malaysian children’s oral health-related quality of life (OHRQOL): A mini systematic review - Ramli, Muhammad Zaki; Nina Suhaity, Azmi (Penerbit UMP, 2022)
Children’s oral health is related to their quality of life. A few instruments have been available worldwide to measure these children’s oral health-related quality of life (OHRQoL). The objective of this article is to systematically review the instruments that have been used to assess Malaysian children’s OHRQoL, from which research gaps could be identified. Articles from Scopus and Web of Science were retrieved, following an advanced search with the following search string: (oral OR dental) AND (child* OR kid* OR (primary dentition)) AND (quality of life) AND Malaysia*), resulting in a final of six shortlisted and reviewed articles based on the review objective. Two valid and reliable instruments were tested and validated, namely Malay Child Oral Impacts on Daily Performances (Malay Child-OIDP) and Malaysian version of Early Childhood Oral Health Impact Scale (Malay-ECOHIS). The Malay Child-OIDP has also been used to assess an indigenous community, namely the children of Semai tribe in Cameron Highlands. Meanwhile, Malay-ECOHIS has a limited use among Malaysian population, compared to the Malay Child-OIDP. Further research among Malaysian children population regarding their oral health-related quality of life should be continued for the benefits of communities at large.